Curcumin induces human cathelicidin antimicrobial peptide gene expression through a vitamin D receptor-independent pathway - Guo, Chunxiao (2012)
The vitamin D receptor (VDR) mediates the pleiotropic biologic effects of 1α,25 dihydroxy-vitamin D(3). Recent in vitro studies suggested that curcumin and poly-unsaturated fatty acids (PUFAs) also bind to VDR with low affinity. As potential ligands for the VDR, we hypothesized that curcumin and PUFAs would induce expression of known VDR target genes in cells. In this study, we tested whether these compounds regulated two important VDR target genes - human cathelicidin antimicrobial peptide (CAMP) and 1,25-dihydroxyvitamin D(3) 24-hydroxylase (CYP24A1)- in human monocytic cell line U937, colon cancer cell line HT-29 and keratinocyte cell line HaCaT. We demonstrated that PUFAs failed to induce CAMP or CYP24A1 mRNA expression in all three cell lines, but curcumin up-regulated CAMP mRNA and protein levels in U937 cells. Curcumin treatment induced CAMP promoter activity from a luciferase reporter construct lacking the VDR binding site and did not increase binding of the VDR to the CAMP promoter as determined by chromatin immunoprecipitation assays. These findings indicate that induction of CAMP by curcumin occurs through a vitamin D receptor-independent manner. We conclude that PUFAs and curcumin do not function as ligands for the VDR.